Brigands M.C. - Muchamore, Robert (London : Hodder Children's Books, 2010)
Dante Scott, still suffering from his family's murder by a biker gang, is given the opportunity to become a member of CHERUB and joins James and Lauren on a mission to infiltrate Brigands Motorcycle Club.
Young Adult
Young Adult
Keywords: Motorcycle clubs -- Juvenile fiction; Teenagers -- Juvenile fiction; Motorcycle clubs -- Fiction; Spies -- Fiction; Teenagers -- Fiction; Clubs -- Fiction; Spy stories; Teenagers -- Fiction; Spy stories